Influence of Skill Acquisition Programmes on Youth Restiveness in Ovia North East Local Government Area of Edo State, Nigeria - Airhuoyo, Faith (My University, 2025)
This study examined the influence of skill acquisition programmes on youth restiveness in Ovia North East Local Government Area of Edo State. Five research questions guided the study. The descriptive survey design was adopted, and 120 youths were selected through simple random sampling. Data were collected using a structured 25-item questionnaire validated by experts, while reliability was established using test–retest technique which yielded a coefficient of 0.75. Data were analysed using mean scores and descriptive statistics. Findings revealed that unemployment, lack of social amenities, poor entrepreneurial capacities, and illiteracy were major causes of youth restiveness (Nsidibe, Emaimo, & Amah, 2017; Ofem & Ajayi, 2008). The study also found a high level of youth participation in entrepreneurship training, vocational programmes, and adult literacy initiatives (Anyanwu, 2002; Oduaran, 1994). Skill acquisition programmes significantly improved youth productivity and reduced involvement in social vices (Ayotunde, 1997; Okeke, 1995). The study concludes that skill acquisition remains a critical tool for curbing youth restiveness. It recommends government-led policies, expanded training access, updated curricula, and post-training support for sustainable youth empowerment.
This article examines the influence of skill acquisition programmes on youth restiveness in Ovia North East Local Government Area of Edo State, Nigeria. Drawing on survey data from 120 youths and using descriptive statistics, the study highlights the major causes of youth restiveness, including unemployment, lack of social amenities, poor entrepreneurial capacity, and illiteracy. It finds that participation in vocational, entrepreneurship, and adult literacy programmes significantly improves youth productivity and reduces engagement in social vices.
Keywords: Vocational Education; Community Development; Your Restiveness; Skill Acquisition Programmes; Youth Empowerment; Entrepreneurship; Youth Studies; Education/Adult Education